Thermal effects investigation during biomass slow pyrolysis in a fixed bed reactor; Biomass and Bioenergy; Vol. 126 - Tabakaev R. B. Roman Borisovich; Astafyev A. V. Aleksandr Vladimirovich; Shanenkova Yu. L. Yuliya Leonidovna; Dubinin Yu. V. Yury Vladimirovich; Yazykov N. N.; Yakovlev V. A. Vadim Anatoljevich (2019, 2019)
Title screen